2018
DOI: 10.1155/2018/5263814
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, Characterization of Some Combined Nanoparticles, and Its Biocide Potency against a Broad Spectrum of Pathogens

Abstract: The development of environmentally benign procedures for the synthesis of metallic nanoparticles (NPs) is a vital aspect in bionanotechnology applications for health care and the environment. This study describes the biosynthesis of Ag, Co, Ni, and Zn NPs by employing nanobiofactory Proteus mirabilis strain 10B. The physicochemical characterization UV-visible spectroscopy, scanning electron microscopy-energy-dispersive X-ray microanalysis (EDX), X-ray diffraction analysis (XRD), transmission electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 53 publications
3
18
0
Order By: Relevance
“…This absorbance rate was due to the surface plasmon resonance (SPR) band of ZnO NPs. This finding was in an agreement with other studies which reported a similar absorption peak [53,54]. According to Eltarahony et al [54], it could be inferred that it was also due to the uniform particle size distribution.…”
Section: O-h Stretching and N-h Asymmetric Stretchingsupporting
confidence: 93%
See 1 more Smart Citation
“…This absorbance rate was due to the surface plasmon resonance (SPR) band of ZnO NPs. This finding was in an agreement with other studies which reported a similar absorption peak [53,54]. According to Eltarahony et al [54], it could be inferred that it was also due to the uniform particle size distribution.…”
Section: O-h Stretching and N-h Asymmetric Stretchingsupporting
confidence: 93%
“…This finding was in an agreement with other studies which reported a similar absorption peak [53,54]. According to Eltarahony et al [54], it could be inferred that it was also due to the uniform particle size distribution. Notably, it was also proven in this DLS analysis study that the biosynthesized ZnO NPs by TA4 cells were monodispersed in nature due to the ideal PDI value obtained at 0.369.…”
Section: O-h Stretching and N-h Asymmetric Stretchingsupporting
confidence: 93%
“…spectroscopy. The AgNPs exhibited light yellow to brown color and it was observed due to excitation of surface plasmon vibration of the metal nanoparticles (25) . The characteristic UV-Vis absorption band maximum present at 420 nm confirmed the presence of spherical or roughly spherical AgNPs.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional method for the synthesis of AuNPs involves the reduction of gold ions by reducing agents such as alkanethiols and alkylamines, or polymeric materials such as polyvinyl alcohol and gelatin to stabilise the AuNPs from aggregation [13]. However the use of capping agents for stabilisation and toxic chemicals for reductions may result in the formation of hazardous by-products, adversely affecting their use in diagnostics [14]. To overcome such limitations, various microbes [15] and biomacromolecules [16] have been used to synthesise AuNPs through redox reactions.…”
Section: Methods Detailsmentioning
confidence: 99%